Automated compared to manual office blood pressure and to home blood pressure in hypertensive patients - Filipovský, Jan; Seidlerová, Jitka; Kratochvíl, Zdeněk; Karnosová, Petra; Hronová, Markéta; Mayer, Otto (Blood pressure, 2016)
We studied the relationships of automated blood pressure (BP), measured in the healthcare centre, with manual office BP and home BP. Stable outpatients treated for hypertension were measured automatically, seated alone in a quiet room, six times after a 5 min rest with the BpTRU device, and immediately afterwards using the auscultatory method. Home BP was measured in a subgroup during 7 days preceding the visit. The automated, office and home BP values were 131.2 ± 21.8/77.8 ± 12.1 mmHg, 146.9 ± 20.8/85.8 ± 12.4 mmHg and 137.7 ± 17.7/79.4 ± 8.2 mmHg, respectively. Limits of agreement between office and automated BP (2 SDs in Bland-Altman plots) were +42.6 to -12.6/+22.6 to -6.6 mmHg for systolic/diastolic BP; for home and automated BP they were +45.8 to -25.8/+20.8 to -12.6 mmHg. For patients with two visits, intraclass correlation coefficients of BP values measured during the first and second visits were 0.66/0.72 for systolic/diastolic automated BP and 0.68/0.74 for systolic/diastolic office BP. Automated BP was lower than home BP and no more closely related to home BP than to office BP. It did not show better repeatability than office BP. Whether automated BP and the "white-coat effect", calculated cas the office BP-automated BP difference, have clinical and prognostic importance deserves further studies.
Keywords: senioři; home blood pressure; krevní tlak; měření krevního tlaku; Hypertension; Prognosis; Middle Aged; mužské pohlaví; Blood Pressure Determination; white-coat effect; ženské pohlaví; prognóza; Blood Pressure; Humans; ambulantní monitorování krevního tlaku; lidé středního věku; hypertenze; blood pressure measurement; Automated office blood pressure; Female; Aged; Blood Pressure Monitoring, Ambulatory; lidé; Male